(3GdGbJUGO GdGLJeGYjs - (3WdYJ GdOeQOGT(B, (3GHQGgjes ((3GdbGgQI(B:s (3ecJHI GdbOS(B,s, 2006)
(3jVe GdQaGgjI GdEbJUGOjI, Gdfeh GdScGfj heSJhi GdeYjTI, Shb GdYed hJCKjQ GdfbGHGJ GdYeGdjI Ydi GdCLhQ, GdHWGdI hCKGQgG GdEbJUGOjI hGdELJeGYjI, GdLQjeI hBKGQgG GdEbJUGOjI hGdELJeGYjI, aQjVI GdRcGI, THcGJ GdCeGf GdEbJUGOj hGdELJeGYj, GdSdY GdNGUI hGdSdY GdYGeI, GbJUGOjGJ GdJdhK GdHjFj, GbJUGOjGJ GdJYde, GdEfaGb GdYScQj hCKGQg GdEbJUGOjI hGdELJeGYjIs
(3HjHdjhZQGajG(B: (3U(B.577s
Keywords: (3GdEbJUGOs; (3GdJfejI GdELJeGYjIs; (3GdJfejI GdEbJUGOjIs